A new genus of Rhaphidophorinae (Orthoptera, Rhaphidophoridae) from China - Qin, Yanyan; Jiang, Huiting; Liu, Xianwei; Li, Kai (Zootaxa, 2018)
In this article, a new genus Sinorhaphidophora gen. nov., three new combinations: Sinorhaphidophora hainanensis (Bian & Shi, 2016) comb. nov., Neorhaphidophora brevispinula (Bian, Zhu & Shi, 2017) comb. nov., Neorhaphidophora longispinula (Bian, Zhu & Shi, 2017) comb. nov. and three new species of Rhaphidophora Audinet-Serville, 1838: Rhaphidophora quadridentata sp. nov., Rhaphidophora setiformis sp. nov., Rhaphidophora wuzhishanensis sp. nov. are proposed. Keys to all genera of Rhaphidophorinae and all species of Rhaphidophora from China are given. And the female of Rhaphidophora sichuanensis Liu & Zhang, 2002 is also added.